”YOUTUBE-SUCCÉN NU I BOKFORM!”: IJustWantToBeCool, Yumi, Tomu och konvergensmaskinen - Olsson, Jakob (Tidskrift för litteraturvetenskap, 2023)
”THE YOUTUBE SUCCESS NOW IN BOOK FORM!” IJustWantToBeCool, Yumi, Tomu and the Convergence Machine In 2022, the two most sold books for children and young adults in Sweden were written by popular content creators on Youtube and other digital platforms. Skurkarnas skurk: Skurkskolan, written by the comedy group IJustWantToBeCool (Joel Adolphson, Emil Beer and Victor Beer) topped the list. In second place came Yumi & Tomu: I Spelmästarens händer, written by the titular Yumi and Tomu (Jenny Laev Alfvén and Tom Karlsson) in collaboration with the author Maria Frensborg. This article examines how these literary works blur the line between children’s literature and internet culture and, therefore, can be understood as examples of contemporary media convergence. Using an intermedial perspective – which focuses on similarities, differences and interactions between media – it is shown how the texts partake in the transmediation of both the identities and storyworlds that the authors have constructed on Youtube. Further, it is shown how they emulate ways in which creators, content and audiences interact on the platform and do so in different ways in the print and audio versions of the books. But other than convergence, Skurkskolan and I Spelmästarens händer also express an interest in the particularities of the printed book. The article ends with a discussion that relates this to today’s discourse surrounding the reading habits of young people. Young people are reading less, and digital technologies and platforms such as Youtube are often seen as parts of the problem. At the same time, the converging of literature and the digital can provide a solution when, for example, popular content creators on Youtube write books that can attract young audiences. Of course, there are economic aspects to this as well as both Youtube creators and book publishers can expand their brands and reach more people by collaborating.